Effect of continuous agriculture of grassland soils of the Argentine Rolling Pampa on soil organic carbon and nitrogen - Milesi Delaye, Luis Antonio; Irizar, Alicia Beatriz; Andriulo, Adrian Enrique; Mary, Bruno (2017)
Long-term soil organic carbon (SOC) and soil organic nitrogen (SON) following cultivation of grassland soils (100/120-year tillage (T) + 20/30-year no tillage (NT)) of the Rolling Pampa were studied calibrating the simple AMG model coupled with the natural 13C abundance measurements issued from long-term experiments and validating it on a data set obtained by a farmer survey and by long-term NT experiments. The multisite survey and NT trials permitted coverage of the history of the 140 years with agriculture. The decrease in SOC and SON storage that occurred during the first twenty years by a loss through biological activity was 27% for SOC and 32% for SON. The calibrated model described the SOC storage evolution very well and permitted an accurate simultaneous estimation of their three parameters. The validated model simulated well SOC and SON evolution. Overall, the results analyzed separately for the T and NT period indicated that the active pool has a rapid turnover (MRT ~9 and 13 years, resp.) which represents 50% of SOC in the native prairie soil and 20% of SOC at equilibrium after NT period. NT implementation on soils with the highest soil organic matter reserves will continue to decrease (17%) for three decades later under current annual addition.